Consensus design : socially inclusive process - Day, Christopher, 1942- (Architectural, 2003)
Consensus Design offers a practical step by step guide to co-design; an increasingly important consideration for architects as they compete for work. The text moves from identifying the methodology of the process to developing a series of principles and practical steps which illustrate how consensus design can be established. For easy reference, flow charts show the process of achieving consensus design and include variations for different types of project and different groups of people. It gives clear timings so that agreements ca.